Preference Erosion and Multilateral Trade Liberalization - Francois, Joseph; Hoekman, Bernard; Manchin, Miriam (Oxford University Press on behalf of the World Bank, 2013)
Because of concern that tariff reductions in Organization for Economic Co-operation and Development (OECD) countries will translate into worsening export performance for the least developed countries, the erosion of trade preferences may become a stumbling block for multilateral trade liberalization. An econometric analysis of actual preference use shows that preferences are underused because of administrative burdens-estimated to be equivalent to an average of four percent of the value of goods traded. To quantify the maximum scope for preference erosion, the compliance cost estimates are used in a model-based assessment of the impact of full elimination of OECD tariffs. Taking into account administrative costs eliminates erosion costs in the aggregate and greatly reduces the losses for countries most affected by preference erosion.